MULTIDISCIPLINARY RESEARCH ON Shorea javanica - E.F. TORQUEBIAU (SEAMEO BIOTROP, 1987)
It was April 1985, under the leadership of Dr. Ir. Z. Goto, then Tropical Forest Biology Program Manager, that it was decided to launch in BIOTROP a multidisciplinary research on Shorea javanica. This followed the publication in 1984 by E.F. Torquebiau of a paper describing the traditional planting of this tree for resin production by farmers near the small town of Krui, in Lampung Province, Southern Sumatra (Man-made dipterocarp forest in Sumatra. Agroforestry Systems, 2: 103-127). A proposal was subsequently made to develop in BIOTROP different research topics around this species in order to promote it for plantation forestry. The choice of this species was justified by the important knowledge from its traditional uses and planting, while in the long term, it is hoped that the development of plantations of this species will promote the use of other dipterocarps and native trees for plantation forestry.